STRUCTURAL EVOLUTION USING SECTION RESTORATION, PHITSANULOK BASIN, CENTRALTHAILAND - Bahae, Weenawadee (Bulletin of Earth Sciences of Thailand, 2021)
The Phitsanulok basin, the largest Cenozoic rift basin in onshore Thailand, is composed of several sub-basins. Most of them are characterized by syn-rift and sag subsidence and distinguished by a limited post-rift unit. The integration of regional 2D seismic interpretation and structural restoration sections were used to define structural geometry variation, extension and subsidence history to improve the understanding of the structure evolution in the basin. The 2D restoration results in possibly six major stages of structural evolution in Phitsanulok basin using the ages referred in PTTEP, 2016: I) Early extension in Early-Oligocene? (>30Ma), II) High extension rate with high subsidence rate, indicates major rifting stage in Late-Oligocene (23 Ma), III) Low extension rate with low subsidence rate, indicates declined stage of rifting in Early-Miocene (18 Ma), IV) Low extension rate with high subsidence rate, indicates sagging process interference in Middle-Miocene (10 Ma), V) Gentle extension rate with gentle subsidence rate, indicates most late stage of rifting or early post-rift stage in late-Miocene (5 Ma), VI) Stable stage indicates Post-rift stage from 5 Ma until present day. The timing of rifting evolution reveals that there is a slightly different timing of events from that commonly applied. The major rifting comes earlier in the Late-Oligocene than Middle-Miocene and continued for a longer time until Late-Miocene. The inversion structure can be observed since Late-Oligocene. There is probably sagging process synchronous with rifting process since MiddleMiocene and most faulting is typically illustrated to die out around the base of Late-Miocene.